From Secondary to Postsecondary: Charting an Engineering Career and Technical Education Pathway. Issue 4 (6th December 2018) - Gottfried, Michael A.; Plasman, Jay Stratte
Abstract: Background: As a whole, the percentage of undergraduates pursuing degrees in science, technology, engineering, and mathematics (STEM) fields has remained constant, a trend of particular concern in the field of engineering. One potential solution for increasing the number of students completing engineering degrees in postsecondary education (PSE), and perhaps closing the gender gap in this area as well, might be through completion of engineering career and technical education (E‐CTE) coursework in high school. Purpose/Hypothesis: This study explores the following questions: What are the characteristics of students who take E‐CTE in high school and the high schools offering these courses? How does E‐CTE in high school connect to engineering degrees in PSE? Does any relationship observed differ by gender? Design/Method: This study utilizes the Education Longitudinal Study of 2002 (ELS) to respond to these research questions. ELS provides a rich array of student and school variables including complete high school and PSE transcripts. The study uses probit regression and a random intercepts model to determine completion of the following engineering outcomes: declared engineering major, AA/AS, BA/BS, MA/MS, and PhD/Doctoral/Professional. Results: This study found that the engineering gender gap is evident in high school, that there are observed connections between E‐CTE in high school and all levels of degree except for AA/AS, and that there is a clear difference across genders as women benefitted more from E‐CTE in connection to completion of an engineering BA/BS than men. Conclusions: This study documents an engineering gender gap in high school and finds that participation in E‐CTE can encourage completion of an engineering degree as well as potentially narrowing the engineering gender gap.